Analisis Determinan Konsumsi Pangan Rumah Tangga Miskin Di Sumatera Barat - Ridho Rahmansyah; Yeni, Isra (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to analyze the determinants of food consumption of poor households in West Sumatra Province. The type of data used is cross section data in 2022 which is sourced from the 2022 National Socio-Economic Survey (Susenas). The initial data of the 2022 Susenas with an individual observation sample of 43760 people, then from the number of observations, a sample of heads of poor households below the poverty line (Rp. 610,941) was obtained, namely 11457 heads of poor households. The research method uses multiple linear regression. The results of the study show that: (1) The education of the head of the household has a significant positive effect on the food consumption expenditure of poor households in West Sumatra; (2) Social assistance also has a significant positive effect; (3) The number of household members has a significant positive effect; (4) Age has a significant negative effect; (5) Gender has a significant positive effect; and (6) Regions have a significant positive influence on the food consumption expenditure of poor households in West Sumatra.